Children in the face of death - Auterio, Antonio (Medicina e Morale, 2024)
The expropriation of death in contemporary Western civilisation has mainly affected children. Through the skirmishes of adults, they have been kept away from the subject and the reality of dying, often out of concern not to disturb the horizon of joy of their childish condition and often also to avoid the resonant blows that can be thrown back from children to adults.